Mapping Research Studies Crowdsourcing Role in The New Era 5.0 - Zahmaya, Raudya Tuzahwa; Santika, Dewi; Setiawan, Adi (International Journal of Engineering, Science and Information Technology, 2025)
Crowdsourcing has emerged as an innovative strategy that utilizes mass collaboration to solve problems, gather ideas, and generate solutions in various fields. This research aims to identify articles that examine the role of crowdsourcing in the new 5.0 era and provide an understanding of crowdsourcing as an innovative approach to marketing. In addition, this research aims to show and explain the mapping of research relevant to the theme. In Industry 5.0, crowdsourcing has entered the marketing world and is starting to be used by some companies. This research uses qualitative methods with bibliometric techniques by utilizing Similarity Visualization (Vosviewers) as an application by entering keywords such as External Stimulus, Cognitive Response, External Stimulus, Opportunity, Barriers, SME, Innovation, Innovator, Knowledge, Digital Sharing to search for articles through Publish or Perish with a total of 346 articles which were then processed using VosViewers. The analysis results found that scientific mapping and the possibility of future research on crowdsourcing can be used as a recommendation variable for future researchers and as a reference for future articles.